DIGITAL MARKETING IN TOURISM DESTINATIONS - Musliha; Adinugraha, Hendri Hermawan (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: The emergence of digital marketing has brought important changes in several industrial sectors, one of which is the tourism industry. This study aims to determine the role of digital marketing in tourist destinations. Methods: The research method used is descriptive qualitative. Results: The result of this study indicates that there are several digital marketing media used by tourists to get information about tourist objects they want to visit, including Facebook, Twitter, Instagram, and other social media. Digital marketing also has a very big influence on increasing visits to several tourist destinations. Conclusion and suggestion: The use of digital marketing in the era of the digital economy industry plays a very important role in increasing tourism promotion. Digital marketing is a must because this generation often uses it, whether consciously or not. Digital marketing applications that will be used include websites, social media, online advertising, web forums, and mobile applications.